How Are People’s Business Credit and Internet Marketing Navigate Micro and Small Industry Performance During COVID-19? : Evidence from Central Java Province - Prasetya, Budianto Oky; Fajri, Moh Najikhul (Universitas Muria Kudus, 2023)
This study analyzes the role of people business credit (KUR)and internet marketing strategy in navigating Medium and Small Industry (MSI’s) Performance. This study uses OLS multiple linear regression to analyze the factors influencing the value of MSI's performance. This study uses cross-section data from the 2020 MSI Survey of Central Java province consisting of 10,782 micro and small business units. In this study, MSI’s performance is measured by the revenue of the Industry. The results show that all explanatory significantly positively affect MSI’s performance, excluding paid labor. In more detail, credit and internet marketing are proven to be effective and have positive implications in influencing the increase in revenue of Industry value to help MSI businesses survive the COVID-19 pandemic storm. The limitation of this study is that it only analyses the income behavior of micro and small business units in Central Java Province without involving large and medium industries. Future research is expected to analyze the role of credit on the soundness indicator of MSI before and after the COVID-19 pandemic in different regions.